Power simulators - a survey / K. Keerthivasan ...[et al.] - Keerthivasan, K.; Deve, V. Sharmila; Krishnaveni, L.; Jerome, Jovitha; Ramanujam, R. (UiTM Press, 2012)
The Power Simulator also termed as Dispatcher Training Simulator (DTS) is used for imparting training in power system operation and allied areas. This paper surveys a good number of literatures on for building an efficient high speed Dispatcher Training Simulator. The purpose of this work is to review and discuss various algorithms of Dispatcher Training Simulator, methodologies to add SCADA / EMS to Dispatcher Training Simulator, assessing the transient stability of the power system, and adding Flexible AC Transmission System devices to improve the performance of the power system. It also enables the readers, the lessons learnt while using Dispatcher Training Simulator. An extensive collection of literature covering modeling of devices for Dispatcher Training Simulator and expert system applications in Dispatcher Training Simulator are also included. This review opens the path for researchers to develop a more sophisticated FAST - Dispatcher Training Simulator with all FACTS devices incorporated in the power system.